Causa Proxima: The Parameters of Perils of the Sea - Wan Talaat, Wan Izatul Asma (1999)
This study is carried out with the purpose of examining the questions of causa proxima and perils of the sea, which is one of the most popular and commonly covered marine risks under the contract of marine insurance. A study on the question of perils of the sea alone, without being connected to the question of causa proxima, cannot be completed nor comprehended because these two key areas in marine underwriting are inextricably woven together. This work reveals that the meaning and application of the doctrine causa proxima non remote spectatur (the proxima and not the remote cause must be looked into) are not as easy as they seem to be. There have been contradictions in the meaning of the words "proximate cause", which circumstantially reflects the inconsistency in the approaches adopted by the courts in construing the words Another difficulty has been found in applying the doctrine where no specific guideline has been introduced, by the relevant statutes or from the judicial precedents, on how the doctrine should be enforced. The tracking made on judicial decisions dealing with these questions has shown that the interpretation and the application of causa proxima were dealt on the individual basis by the judges without looking further back. Another revelation by this work is on the parameters of the term "perils of the sea", which had become unclear due to the two detected problems i.e. the inconclusive meaning of perils of the sea and the indefinite extent of perils enumerating the term. This work has been carried out with the commitment and determination to solve the above unresolved problems. The study conducted was carried out with the purpose of finding the best solutions to those problems coupled with the hope to provide clearer and more definitive answers to them. This paper is laid down in five chapters. The first chapter deals with Introduction, which speaks of marine briefly on the contract insurance as well as on the problem statement and methodology of the study. The second chapter comprises of two main areas; the first one deals with the doctrine of causa proxima, it's meaning and application while the second area deals with perils of the sea and the exclusions for the purpose of looking into the meaning of perils of the sea and it's boundary.Under Chapter Three and Four, a review and analysis of the problems, which are extracted from numerous cases and opinion of various scholars, are revealed that are hoped to provide clearer, if not definite, answers to problems stated in chapter one. Under the third chapter, the meaning and application of causa proxima are once again dealt with while the fourth chapter, by exposing the reviewed meaning of the expression "perils of the sea" as well as listing down the established perils enumerating the range of perils of the sea and the limits to such range, explicitly divulges with clearer parameters of the expression. The final chapter comprises of two main parts; the summary deals with the problems detected and the findings to those problems and the second part, the conclusion, deals with the assessment and analysis founded from the study conducted